Effect of the polarity of reaction medium and electric field on zwitter-ion polymerization of methacrylonitrile - Ranogajec, Franjo (Array, 2009)
Istraživan je mehanizam polimerizacije metakrilonitrila inicirane trietilfosfinom u dimetilformamidu i tetrahidrofuranu.